Bioactive compounds, antioxidant, xanthine oxidase inhibitory, tyrosinase inhibitory and anti-inflammatory activities of selected agro-industrial by-products - Oskoueian, Ehsan; Abdullah, Norhani; Hendra, Rudi; Karimi, Ehsan (Multidisciplinary Digital Publishing Institute, 2011)
Evaluation of abundantly available agro-industrial by-products for their bioactive compounds and biological activities is beneficial in particular for the food and pharmaceutical industries. In this study, rapeseed meal, cottonseed meal and soybean meal were investigated for the presence of bioactive compounds and antioxidant, anti-inflammatory, xanthine oxidase and tyrosinase inhibitory activities. Methanolic extracts of rapeseed meal showed significantly (P < 0.01) higher phenolics and flavonoids contents; and significantly (P < 0.01) higher DPPH and nitric oxide free radical scavenging activities when compared to that of cottonseed meal and soybean meal extracts. Ferric thiocyanate and thiobarbituric acid tests results showed rapeseed meal with the highest antioxidant activity (P < 0.01) followed by BHT, cotton seed meal and soybean meal. Rapeseed meal extract in xanthine oxidase and tyrosinase inhibitory assays showed the lowest IC50 values followed by cottonseed and soybean meals. Anti-inflammatory assay using IFN-γ/LPS stimulated RAW 264.7 cells indicated rapeseed meal is a potent source of anti-inflammatory agent. Correlation analysis showed that phenolics and flavonoids were highly correlated to both antioxidant and anti-inflammatory activities. Rapeseed meal was found to be promising as a natural source of bioactive compounds with high antioxidant, anti-inflammatory, xanthine oxidase and tyrosinase inhibitory activities in contrast to cotton and soybean meals.